Dynamique et performances des dépenses publiques en Algérie : un réexamen: Dynamics and performance of public expenditure in Algeria: a review - ZIAD M’hamed (Journal of North African Economies, 2025)
The objective of this paper is to determine the impact of public spending on macroeconomic performance in Algeria, taking into account growth rates. Using annual data covering the period (1992-2019), the VAR model regressions reveal a positive relationship between economic fundamentals and the dimension of government intervention designed by budgetary stimulus plans adopted since 2001. This result can undoubtedly be explained by the role of regulator and stabiliser of the overall economic activity played by the State on the national scene, especially when serious threats of cyclical imbalances are looming. Given these specificities of the Algerian economy, it is likely that these results cannot be generalised, and that these tests do not allow us to highlight a significant causality between public spending and economic growth.